Pattern of Foreign Trade in Nepal - Bhagat, Sadan Kumar (Tribhuvan University Journal, 2020)
Most of the countries in the world strengthen their economic and political power with the help of foreign trade and it is advantageous for both importing and exporting countries. The situation of foreign trade is not good in Nepal. Nepal has imported almost 15 times greater than its export amount in Fiscal Year 2018/19.The import amount of only petroleum products was 2.62 times greater than its total export amount. The major contributors of foreign trade were India and China which covered 64.70 percent and 13.70 percent market share respectively during FY 2018/19. The objectives of this study were to examine the situation of foreign trade in Nepal, to highlight its positive aspects and to analyze the problems along with some measures to resolve the problems. To examine the situation of foreign trade in Nepal secondary data have been collected from government publications and analyzed after presenting in tables. Likewise, a cross-section of 50 respondents from various cities have been interviewed to collect primary data. Nepal was always in trade deficit which was increasing every year. Remittance inflow from migrant labors was a major source of foreign exchange which covered the payment of imported goods. The problems of foreign trade were landlocked country, transit and transport problems, illegal import-export, low value addition exportable commodities, incompetent Nepalese products in terms of cost and quality, poor physical infrastructure, industrial dependency on imported raw and intermediate materials, procedural problems created by foreign countries in the import-export of products, administrative hurdles etc.